The Objectives and Aims of a Modern Special Library With Reference to the Ghanaian Situation - Annoh, Grace (Ghana Library Journal, 2000)
The paper discusses the na ture of special libraries. It explains the meaning of a mod ern special library as one with modern library facilities and equipment and employing modern methods of in formation s torage and retrieval systems. The objectives and a ims of a modern special library are stated and the strategies and services which must be ad opted in order to achieve them are discussed. The relevance of the objectives and aims are discussed with regard to the Gha naian situation .